Politeness in the Use of Language in Social Media - Chandra Oktiva Herry (EDP Sciences, 2021)
The use of social media in communication changes the way people express the idea represented through their language. This study aims to seek for the form of communication patterns in social media and to reveal causes of specific pattern language usage found in media, especially in office domain. The study was conducted using descriptive qualitative by describing the results of observations, interviews, and documentation. The data were collected by non-participatory observation method and note taking technique. Based on the results of the analysis of the data, it can be concluded that the communication patterns are realized in the form of: (1) various forms of language which do not meet the standard language, (2) the use of other non-verbal representations, such as emoticon, and (3) ecrononciation, that is, writing the spoken language. The choice of utterances is affected by relative status, social distance and range of imposition. As communicating to others, most utterances represent the obedience to politeness maxim, namely be friendly (sumanak), be considerate (tepa slira), suitable topic to event (empan papan), and pleasant voice true and good temper (nuju prana).